A Comprehensive Study of the Physical Properties of Actinide-based Advanced Nuclear Fuel Materials, UX (X = C, N, O): A DFT Insight - Karmkar , R. C.; Ahmed, E.; Sarker, B. K.; Ahmed, S.; Hossain, F.; Hossain, M. T.; Sheikh, M. A. R. (Journal of Scientific Research, 2026)
This investigation analyzes the fundamental physical properties of UX (X = C, N, O) using the density functional theory-based CGA-PBE and CGA-PBEsol functionals implemented in the CASTEP code. The obtained lattice parameters of UX using the CGA-PBEsol technique demonstrate good agreement with previously reported results, and further calculations have been performed based on this technique. The electronic structure analysis reveals the metallic nature of UX. The dynamical stability of the studied structures has been checked through their phonon dispersion curves. The mechanical stability and ductile behavior of the studied compounds have been confirmed by the Born stability criterion, Cauchy pressures, Pugh’s ratio, and Poisson ratio. For the first time, the famous Slack equation has been utilized to calculate the lattice thermal conductivity of the studied compounds. From the thermophysical analysis, it is observed that UC has exhibited the highest Debye temperature and lattice thermal conductivity (kL) at room temperature, while UN has the highest melting temperature. Furthermore, UC and UN have displayed the lowest thermal expansion. Overall, this extensive study on the physical properties of UX (X = C, N, O) reveals the potential application of UC and UN solid fuel materials in nuclear power plants.